2001
DOI: 10.1111/j.1439-0434.2001.tb03871.x
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Dependent Accumulation of Tryptamine in the Rice Sekiguchi Lesion Mutant Infected with Magnaporthe grisea

Abstract: An antifungal compound with an infection-inhibiting activity was isolated from a rice Sekiguchi lesion (sl) mutant and identi®ed as the indole alkaloid tryptamine. Tryptamine inhibited not only spore germination and appressorium formation of Magnaporthe grisea at high concentrations (> 600 lg/ml) but also the infection hypha formation in onion cells at low concentrations (150±300 lg/ml). Tryptamine is a normal compound of the rice sl-mutant but accumulates further in rice with a mutant-type response (Sekiguchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…However, tryptamine did not accumulate in rice with blast lesion formation. These results suggested that tryptamine plays an important role in light-enhanced resistance in the rice Sekiguchi lesion mutant (Arase et al 2001). …”
Section: Introductionmentioning
confidence: 94%
“…However, tryptamine did not accumulate in rice with blast lesion formation. These results suggested that tryptamine plays an important role in light-enhanced resistance in the rice Sekiguchi lesion mutant (Arase et al 2001). …”
Section: Introductionmentioning
confidence: 94%
“…72 The deficiency of serotonin in rice plants could have secondary effect on other organisms in the paddy ecosystem. In addition to the increased resistance to insect pests BPH and SSB, Arase et al 73 showed increased resistance to Magnaporthe grisea under light. In addition, Ishihara et al 74 observed that the Sekiguchi lesion mutant became more susceptible to Bipolaris oryzae infection than its parent.…”
Section: The Tradeoffs Of Ost5h Knockoutmentioning
confidence: 99%
“…Sekiguchi-asahi was grown in a greenhouse as described previously by Arase et al (2001). Virulent strain (Naga 69-150, race 007) of M. grisea was grown on rice bran agar medium at 26°C for 14 days.…”
Section: Plant Pathogen and Inoculationmentioning
confidence: 99%
“…Previously, we isolated an indole alkaloid, tryptamine, from a Sekiguchi lesion, but not from healthy tissues, as a possible factor in the light-enhanced resistance of the rice sl mutant (Arase et al 2001). Tryptamine inhibited not only spore germination and appressorium formation by M. grisea at high concentrations ([600 lg/ml) but also infection hypha formation in onion cells at low concentrations (150-300 lg/ml).…”
Section: Introductionmentioning
confidence: 99%